2003
DOI: 10.1557/proc-791-q8.26
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coupling Agent on the Dispersion of PETG Montmorillonite Nanocomposite films.

Abstract: Polyethylene terephthalate glycol (PETG) is a clear amorphous polymer, which is extensively used in flexible packaging. The dual packaging requirements of recyclability and long-term shelf life are often difficult to achieve. Meeting these needs become more urgent when considering food packaging for large volumes of soldiers positioned in different parts of the world. Our approach is to develop a high barrier PET packaging system via the Montmorillonite layered silicate (MLS) based nano technology. Prior resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
3
1
0
Order By: Relevance
“…The first diffraction peaks (001) d-spacings for both of these intercalated nanocomposites were narrow, indicating a strong intercalated behavior and a high stacking order of the successive clay layers in the nanocomposites. Similar occurrences were observed by Kumar et al [26] and Ranade et al [27] The higher clay content of 7 wt % tended to have the same diffraction profile, with a slightly higher first diffraction peak (001) d-spacing angle at 2θ = 3.86°. However, the broader peak indicated some level of reduction in the clay platelets per stack in the polymer matrix.…”
Section: Structural Properties Of Ts/pla/cloisite Na + Nanocompositessupporting
confidence: 85%
“…The first diffraction peaks (001) d-spacings for both of these intercalated nanocomposites were narrow, indicating a strong intercalated behavior and a high stacking order of the successive clay layers in the nanocomposites. Similar occurrences were observed by Kumar et al [26] and Ranade et al [27] The higher clay content of 7 wt % tended to have the same diffraction profile, with a slightly higher first diffraction peak (001) d-spacing angle at 2θ = 3.86°. However, the broader peak indicated some level of reduction in the clay platelets per stack in the polymer matrix.…”
Section: Structural Properties Of Ts/pla/cloisite Na + Nanocompositessupporting
confidence: 85%
“…The decrease in T g with the addition of organoclays 25A and 15A could have been due to their plasticizing effects on the TS/PLA chains. Ranade et al (2004) reported similar results in their work. Figure 10 shows typical DSC thermographs of the first heating scans with the distinct endothermic peaks (T m ) of the foams.…”
Section: Thermal Properties Of Ts/pla /Clay Nanocomposite Foamssupporting
confidence: 79%
“…The first diffraction peak (0 0 1) d-spacing for the intercalated nanocomposite was narrow, indicating a strong intercalated behavior and a high stacking order of the successive clay layers in the nanocomposites. Similar occurrence also was observed by Kumar et al (2003) and Ranade et al (2004). The second diffraction peak occurred at 2θ = 5.16°, appeared smaller and weaker, and was due to the second registry (0 0 2) d-spacing of the organoclay (Ray et al, 2002;Pluta, 2004).…”
Section: Structural Properties Of Ts/pla/clay Nanocomposite Foamssupporting
confidence: 63%
“…[33] A methyl tallow bis(2-hydroxyethyl) ammonium organic modification led to better dispersion than octadecylamine or dodecylamine modifications. [34] In the case of 1,4-cyclohexanedimethanol-terephthalic acid-ethylene glycol copolymer (PETG), the effects of the organoclay presence on the viscoelastic properties [35] and on the properties of its films [36,37] were studied. However, to our knowledge, no work has been published based on PCTG, which is a copolymer with the same components as those of PETG, but with different proportions of the chemical groups.…”
Section: Introductionmentioning
confidence: 99%